(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1916)
Four rectangular stone structures are surrounded by a roughly circular stone wall. The structures have passageways leading into them and internal features including hearths and possible benches or beds. A few small fragments of wheel-thrown pottery and limpet shells were found.